Improving teaching and learning in undergraduate science: Some research and practice - Zadnik, Marjan; Yeo, Shelley (UniServe Science, 2001)
Research has shown that traditional methods of teaching science (lectures, laboratories and problem solving tutorials) are ineffective in promoting conceptual change and are inadequate or unsuitable for many students. Together with a growing number of colleagues around the world, members of the Physics Education Research and Development Group at Curtin University of Technology have attempted to address some of these issues by incorporating, or developing and evaluating, innovative teaching practice in their courses. Teaching innovations, such as the implementation of a 'studio' Model, are being researched to examine their effectiveness in changing students’ understandings of fundamental concepts. These innovations integrate theory, experiment and problem solving activities in a student-centred 'hands-on' learning environment based on a constructivist epistemology. This paper discusses some of the reasons for embarking on research into university science teaching and learning. It outlines the guiding principles and then describes some of the current projects and lessons we have learnt, which have led to improvements in student learning.